(untitled) (Academic Journal of International University of Erbil, 2025)
Corporate social responsibility is examined in this study. The implementation of Corporate Social Responsibility and strategic management accounting offers a means to enhance organizational performance that promotes sustainable development through the use of effective planning strategies. Consequently, the research concentrates on qualitative data obtained from interviews and field questionnaires and highlights crucial factors such as cause, context, and action that can have an impact on corporate social responsibility and strategic management accounting. These results imply that companies who adopt a more inclusive approach, taking into account these two concepts, will have significantly better social and environmental outcomes, leading to improved economic performance and stakeholder confidence. It emphasized the importance of ethical management practices and how industries contribute to social and ecological footprints.? Through community development and the reduction of inequalities, companies can fulfill their ethical responsibilities while also ensuring long-term viability and competitive advantages.